THE EUROPEAN UNION IN THE LIGHT OF COMPARATIVE POLITICS - Danuta Kabat-Rudnicka (Сравнительная политика)
Abstract: In the academic literature the European Union (EU) is analysed from different theoretical perspectives. Taking the perspective of international relations, the EU emerges as an international organization or a confederation; on the other hand, looking from the perspective of comparative politics, the EU presents itself as a more integrated entity, a federation, a quasi-state or a state in the making. The recent perspective, i.e. the governance school, sees the EU as an original structure, a sui generis entity, a new, emerging system of governance without government. However, at the present stage of development, the EU reveals features that are characteristic for the federal structure, i.e. the federal political system characterised by two leading models of dual and cooperative federalism, hence the comparative method seems to be the most appropriate as a research tool.